(untitled) (LACCEI, 2024)
In the construction sector, contracts are constantly tested by the contracting party and the contractor, deficiencies in these often mean that the expectations of each party are not satisfied, leading to litigation that negatively affects the relations between the parties. This document proposes a case study of a representative construction company in the construction industry, where contracts for reimbursable costs are not generating the expected profits. 16 managers were surveyed and the contracts for this typology were studied where initially a diagnosis of the company was made regarding the behavior in this type of contracts, deviations and those practices that have generated good results were identified, from the above a model in which for each stage of the life cycle a manager can identify and apply these good practices and thus reduce the probability of economic losses for the contractor company.